Co-création de valeurs partagées pour redynamiser une région de montagne à travers le tourisme nocturne : étude de cas en Suisse romande - Vincent Grèzes; Rafael Matos-Wasem; Sandra Grèzes (Revue de Géographie Alpine)
The Val d’Anniviers, a relatively peripheral valley in the Valais Alps has been at the heart of an applied research project seeking to reinvigorate its tourism. In fact, the School of Management and Tourism in Sierre via its Entrepreneurship, Management and Tourism Research Institutes, has set into motion a process of co-creation bringing together institutional, economic and tourism actors from the region enabling the conception of a novel tourism offer which could be of interest to part of the potential clientele. The product, the creation of the “Star Park”, is a likely candidate for success thanks not only to a location and a topography conducive to star gazing but also thanks to the presence of the village of St. Luc situated in the same valley, as well as an observatory and a trail of the planets which reproduces the solar system on a human scale. What is more, there is a clearly increasing demand at present for original products involving deceleration, stresslessness and going back to nature, all trends which are to be found in the proposed starry sky offer which aims to facilitate star gazing by reducing light pollution. This article presents the methodology used in this co-creation process within its historical, economic, social, and environmental contexts so that it may be reproduced elsewhere with regard for local conditions.